Extravasation of Noncytotoxic Drugs. Issue 8 (August 2020) - David, Valentin; Christou, Niki; Etienne, Pauline; Almeida, Martine; Roux, Alexia; Taibi, Abdelkader; Mathonnet, Muriel
Objective: Commonly used drugs may be dangerous in case of extravasation. The lack of information from health care teams can lead to delays in both diagnosis and treatments. This review aims at alerting health care professionals about drugs and risk factors for extravasation and outlines recommendations for the diagnosis and treatment of extravasation.Data Source: A literature search of MEDLINE/PubMed, Scopus, the Cochrane Library, and Google Scholar was performed from 2000 to December 2019 using the following terms: extravasation, central venous line, peripheral venous line, irritant, and vesicant .Study Selection and Data Extraction: Overall, 140 articles dealing with drug extravasation were considered potentially relevant. Each article was critically appraised independently by 2 authors, leading to the inclusion of 80 relevant studies, guidelines, and reviews. Articles discussing incidents of extravasation in the neonatal and pediatric population of patients were excluded.Data Synthesis: Training of health care teams and writing care protocols are important for an optimal management of extravasations. A prompt consultation should be achieved by a specialist surgeon. The surgical procedure, if necessary, will consist of wound debridement followed by an abundant lavage.Relevance to Patient Care and Clinical Practice: This review discusses the management of drug extravasations according to their mechanism(s) of toxicity on tissues. It highlights the importance of a close monitoring of patients and the training of health care teams likely to face this type of adverse event.Conclusions: Extravasations still contribute to significant morbidity and mortality. A good knowledge of risk factors and the implementation of easily and quickly accessible standardized care protocols are 2 key elements in both prevention and treatment of extravasations.